Merger announcements and share price return: The role of the relationship between acquiring and target firms - R. C. Van Den Honert; G. D.I. Barr; J. F. Affleck-Graves; G. Smale (South African Journal of Business Management, 1988)
The authors examine, in a cumulative average abnormal return (CAAR) framework, the effect of four easily identifiable features of merger activity on acquirer/target shareholder wealth. The features considered are the relatedness of the acquiring and target firms involved in the merger, the relative sizes of the acquirer and target, the prior control position, and the medium of exchange. The results indicate that the relatedness of the acquirer and target firm and the prior control position are strong factors in determining the distribution of any wealth effects between the shareholders of the target and acquiring firms. The size and the medium of exchange are shown to be weaker factors in determining the distribution of wealth. In all cases it is seen that the shareholders of acquiring firms do not tend to benefit in the short term from the merger while those of the target firms show significant gains.
Keywords: 650